2009
DOI: 10.1177/1477153509104013
|View full text |Cite
|
Sign up to set email alerts
|

Towards the third stage of the lighting profession

Abstract: The notion of stages of the lighting profession is examined to identify the main themes that have directed the objectives of the lighting profession. It is proposed that the objective of the first stage was provision of uniform illumination over a horizontal plane, and that of the second stage has been to provide illuminance suited to human need, based on visual performance. This brings us up to the current era, and it is the author’s opinion that the second stage has failed to achieve its objective. While cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
123
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(129 citation statements)
references
References 15 publications
2
123
0
4
Order By: Relevance
“…However, Cuttle [23] is clear that while this level of light may be sufficient for "performance" it is inadequate for "appearance". Furthermore, using the level of light on a working plane is not a representative measure with which to assess appearance since perception of lighting is based on the light that "exits" all surfaces in a room (luminence) rather than the light level that "arrives" at a certain point in a room (illuminance).…”
Section: Ieq Indicators For a Visual Environmentmentioning
confidence: 99%
See 3 more Smart Citations
“…However, Cuttle [23] is clear that while this level of light may be sufficient for "performance" it is inadequate for "appearance". Furthermore, using the level of light on a working plane is not a representative measure with which to assess appearance since perception of lighting is based on the light that "exits" all surfaces in a room (luminence) rather than the light level that "arrives" at a certain point in a room (illuminance).…”
Section: Ieq Indicators For a Visual Environmentmentioning
confidence: 99%
“…These assumptions have been challenged for many decades [22] but more recent research has demonstrated the flaws in assuming that the appearance of lighting in a space can be measured by a level of light on a working plane and that more light necessarily results in improved appearance or performance [23]. This research exposes that there were no empirical studies carried out to justify the basis for commonly recommended light levels in offices; they were based on "reason rather than research" [23] (p. 77).…”
Section: Ieq Indicators For a Visual Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Simply following them will not produce good quality lighting. Boyce [12] explores methods which may bridge the gap between indifferent and good quality lighting such as proposals by Cuttle [13][14][15][16][17][18][19] and proposes that if none of these are accepted and adopted in the future, then good quality lighting will only be available to those who can afford the services of a creative, experienced and talented lighting designer.…”
Section: Limitations Of Standardsmentioning
confidence: 99%